Land Conflicts in Emerging Suburban Areas in Viet Nam: Causes and Effects - DO, THANH-HUYEN (Local Administration Journal, 2020)
This research takes the initial steps toward understanding the causes and effects of land conflict in Viet Nam after the enactment of the 2003 Land Law and its subsequent amendments in 2013. It examines institutional arrangements that govern land rights security but may have created biases toward different land users when there are conflicting land-use purposes. The paper draws upon data from two large sample surveys in Viet Nam (the citizen-perception-based Vietnam Provincial Governance and Public Administration Performance Index and the firm-perception-based Provincial Competitiveness Index) in informing potential treatments towards citizens and firms as land users. The findings presented in this article imply more work needs to be done to improve land transparency for citizens, who play critical roles in securing regime legitimacy and contributing to the sustainable development of Vietnam. It also suggests the need for a more level playing field for the society and the market in relation to the State in land governance to mitigate potential conflicts in Vietnam